Hertzian Load-bearing Capacity of Hybrid and Nano-hybrid Resin Composites Stored Dry and Wet - Farmani S; Orandi S; Sookhakiyan M; Mese A (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Hertzian indentation test has been proven to be an efficient and reliable alternative upon Vickers hardness test. This method has been used to test dental ceramics, amalgams, glass ionomers and luting cements.There is limited published information about the load-bearing capacity of resin composites using Hertizian indentation test. Objectives: To investigate the load-bearing capacity of hybrid and nano-hybrid resin composites stored dry or wet up to 30 days, using Hertzian indentation test. Materials and Methods: Three resin composites were used: two nano-hybrids (Filtek Supreme, and Luna) and one hybrid, (Rok). A total of 108 disc-shaped specimens (1mm thick x 10 mm diameter) were prepared using polyethylene mould. The specimens of each material were randomly divided into 6 groups of 6 (n=6) and stored at 370C either in distilled water or dry for 1, 7 and 30 days. The specimens were tested using Hertzian jig aligned in the universal testing machine. The specimen was placed on the top of a disc-shaped substrate. The load was applied at the center of each specimen and the load at the first crack was recorded. Data were analyzed by ANOVA, Tukey'sand student's t-test using SPSS version 18.0. Results: Three-way ANOVA showed a significant interaction between all the factors (p = .0001). The load bearing capacity of almost all materials reduced significantly in the wet condition in comparison with the dry condition (p = .0001). After seven days of immersion in distilled water, Filtek Supreme had significantly lower values than those of Rok and Luna, there was no significant differences between materials in the dry condition. Conclusions:In contrast to dry condition, the load-bearing capacity of specimens stored in distilled water decreased significantly over the 30 days of immersion. The load bearing capacity of nano-hybrid composites tested in this study was shown to be comparable with that of the hybrid composite.